Uma abordagem de desenvolvimento solo de aplicações utilizando princípios ágeis - Previato, Erick Vansim (Universidade Federal de São Carlos, 2018)
The application development market has been growing over the years, thereby, companies always seek to use development methodologies that increase productivity and team interaction, decrease the cost and development time, without losing the quality of the final product. In addition, several people try to work in this market, but does not have the necessary resources to hire a team. Thinking about this scenario, this paper proposes a study of the solo development methodologies that follow agile principles, and also proposes a new approach to solo development. As a result, is presented if it is possible to adopt agile methodologies in solo software development. It is also showed a new development approach based on agile Scrum and XP methodologies, but adapted for individual use. In order to validate a proposal, two pilot projects were developed for the implementation of the methodology, and the results of this application are explored in order to know whether such an approach is viable or not.
Keywords: Metodologias de desenvolvimento; Métodos ágeis; Desenvolvimento solo; Scrum; Development methodologies; Agile methods; Solo development; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO